KAJIAN KONDISI BIOFOSIK LAHAN DAERAH ALIRAN SUNGAI DI SUBDAS CIUJUNG HULU, PROVINSI BANTEN - Egidius Naitkakin; Latief Mahir Rachman; Yayat Hidayat (Jurnal Hutan Tropis, 2021)
The upstream of a watershed is a buffer zone and it protects the whole watershed. The degradation of a watershed is caused by uncotrolled uses of the land and exploitation of the nature resources such as forest, land, and water. It causes the changes in the carrying capacity of the watershed, especially in biophysical aspects. This research aims to study the watershed biophysical condition in Ciujung Hulu Watershed, Banten Province. Biophysical condition analyzed using Forestry Minister Regulation P.61/Menhut-II/2014 for degraded land class, land cover percentage, and Erosion Hazard Index. The condition of the land, such as degraded land, vegetation cover, and erosion index, analyzed using modification of Forestry Minister Regulation Perdirjen BPDAS PS Nomor P.4/V-SET/2013. The result of the study showed that the percentage of degraded land, vegetation cover percentage, and erosion index were 25,85% (severe degraded land), 9,77% (very low covered), and 30,89 (Very high).